Methods of liquid evaporation on the basis of acoustic-vacuum and thermal influences (overview) - O. L. Prusova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The basic effects and their combinations on evaporated liquid located on solid surface and in the form of a suspended droplet are analyzed. Methods of applying these effects for liquid evaporation under the following boundary conditions of the liquid location: «drop», «film» are considered. The classification of one-, two-, and three-factor effects on the evaporated liquid is proposed. The direction of further research in the field of joint application of convective, conductive and vacuum influences on the dried object is formulated